2019
DOI: 10.9734/jpri/2019/v30i630285
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cytotoxic and Anti-HIV Potential of Triphala Herb Mixture on from Chae Son, Lampang, Thailand

Abstract: Introduction:  The objective of this study was to compare the stability properties of the two years for the quality of Tri-Pha-La Herbal Drink, Thai traditional and Ayurvedic medicine. This study aimed to compare the anticancer and anti-HIV efficacy of the solvent extracts and gallic acid of the three fruits. The research was done between A.D. 2017 to A.D. 2018. Materials and Methods: In the present study, the cancer cell lines, KB, HT 29, MCF-7, A 549, CL and ASK treated with Triphala fruits extract at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Anti-HIV1-RT testing of the extracts of P. phuyensis and isolated compound were carried out at the Service Centre of the Department of Physiology and Microbiology, Mahidol University, Thailand .The anti-HIV1-RT activities were performed by testing RT inhibition. 15,16,17 The extracts were diluted to give 20 mg/mL of 100% dimethyl sulfoxide (DMSO) after the removal of tannin by polyvinylpyrrolidone (PVP). The final volume was 200 μg/mL in 10% DMSO, and Nevirapine, 2 μg/mL was used as a positive control.…”
Section: Hivs Assay Anti-hiv1-rt (Reverse Transcriptase Assay)mentioning
confidence: 99%
“…Anti-HIV1-RT testing of the extracts of P. phuyensis and isolated compound were carried out at the Service Centre of the Department of Physiology and Microbiology, Mahidol University, Thailand .The anti-HIV1-RT activities were performed by testing RT inhibition. 15,16,17 The extracts were diluted to give 20 mg/mL of 100% dimethyl sulfoxide (DMSO) after the removal of tannin by polyvinylpyrrolidone (PVP). The final volume was 200 μg/mL in 10% DMSO, and Nevirapine, 2 μg/mL was used as a positive control.…”
Section: Hivs Assay Anti-hiv1-rt (Reverse Transcriptase Assay)mentioning
confidence: 99%
“…MBC was only employed for the lowest concentration of the bacteria that did not retrieve 2 single colonies. [10] Anti-HIV1-RT and cytotoxicity assay of the extracts of Milletia phuwuaensis were conducted at the Service Centre of Department of Physiology and Microbiology, Mahidol University, Thailand. The anti-HIV1-RT activities were decided by testing RT inhibition [11,12].…”
Section: Minimum Bactericidal Concentration (Mbc) [9]mentioning
confidence: 99%
“…An anti-HIV1-RT activity assay, anti-syncytium test and cytotoxic study were done as reported by Pompimon, W., et al [4,5] and Limjiasahapong, S., et al [6].…”
Section: Anti-hivs Assay and Cytotoxic Studymentioning
confidence: 99%